2019
DOI: 10.4103/ijabmr.ijabmr_89_19
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and medicolegal significance of wormian bones in human skulls in North India Region

Abstract: Introduction: Wormian bones (Wbs) are small bones located in or near the sutures of the skull which are irregular in size, shape, and number. The present study is to look into the morphological details of such supernumerary bones of skull with regards to their incidence, number, and topography in skulls from the Haryana region. Materials and Methods: This observational study was carried out in the tertiary care hospital, in the region of Haryana and the total of 147 hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…We have known of wormian bones for a very long time. 9,11,12 In our study, incidence of the wormian bones was found to be 20.78%. The incidence of wormian bones varies in the literature.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…We have known of wormian bones for a very long time. 9,11,12 In our study, incidence of the wormian bones was found to be 20.78%. The incidence of wormian bones varies in the literature.…”
Section: Discussionsupporting
confidence: 49%
“…16 Simlarly, Marti et al and Goyal et al in their respective studies also showed maximum incidence of wormian bones along with lambdoid suture. 4,12 In the present study, the second most common site of wormian bone was at sagittal suture (5.38%). Only 1 (0.77%) case showed wormian bone in coronal suture.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…There are different hypotheses that these ossicles are mechanically induced and that they are associated with genetic defects (3). Because of their unusual appearance, these ossicles can be misdiagnosed as fractures during radiographic imaging, which is one of the reasons why these ossicles are clinically important (12,13). Although WBs can also be observed in healthy individuals, they are known to be associated with some cranial or central nervous system disorders (14).…”
Section: Discussionmentioning
confidence: 99%
“…Localization of the WBs is important not only for anatomists but also for anthropologists, radiologists, and causality medical officers. Moreover, in autopsy surgery, knowledge of WBs is essential for the correct identification of traumatic fractures of the skull or (12). Despite their clinical significance, limited studies have been done on the number and topographic distribution of WBs in the Anatolian population.…”
Section: Introductionmentioning
confidence: 99%